2014
DOI: 10.1111/1469-0691.12333
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus bovis group and biliary tract infections: an analysis of 51 cases

Abstract: Streptococcus bovis is a well-known cause of endocarditis, but its role in other infections has not been well described. We analysed prospectively all patients with biliary tract infections caused by S. bovis group during the period 1988-2011. We selected those cases associated with cholangitis and cholecystitis, defined according to Tokyo guidelines. Identification of the strains was performed using the API 20 Strep and the GP card of the Vitek 2 system, and was confirmed by molecular methods. Our series incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
0
32
0
3
Order By: Relevance
“…The non-colonic cancers were more often found in the pancreas or biliary tract. In a later study Corredoira et al (2014b) even found that the prevalence of colorectal neoplasia in patients infected with SB II does not appear to be higher than the prevalence among the general population and therefore suggested that colonoscopy should not routinely be performed in these patients. We found a statistically significant association between S. gallolyticus subsp.…”
Section: Discussionmentioning
confidence: 94%
“…The non-colonic cancers were more often found in the pancreas or biliary tract. In a later study Corredoira et al (2014b) even found that the prevalence of colorectal neoplasia in patients infected with SB II does not appear to be higher than the prevalence among the general population and therefore suggested that colonoscopy should not routinely be performed in these patients. We found a statistically significant association between S. gallolyticus subsp.…”
Section: Discussionmentioning
confidence: 94%
“…Different microbiological classification of S. bovis subspecies may have various relationships to colorectal neoplasia in adults ( 8 , 18 , 19 ). Patients infected with S. gallolyticus subsp gallolyticus (biotype I) were noted to have an increased rate of colorectal neoplasia and infective endocarditis ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, it is increasingly recognized as a cause of infant meningitis and bacteremia [9,10,11,12], and 58.7% of mortality rate has been observed with one-year neonates relating to this subspecies [13]. In adults, it is linked to a wide spectrum of diseases, including meningitis [14], endocarditis [15,16,17], splenic abscess [18], biliary and urinary tract infection [15,19,20,21], as well as gastric, pancreatic, hepatobiliary and colorectal cancers [16,22]. Death cases in adults were also reported in association with infections by this subspecies.…”
Section: Introductionmentioning
confidence: 99%